2008
DOI: 10.2139/ssrn.1305280
|View full text |Cite
|
Sign up to set email alerts
|

Is Employer-Based Health Insurance a Barrier to Entrepreneurship?

Abstract: The focus on employer-provided health insurance in the United States may restrict business creation. We address the limited research on the topic of "entrepreneurship lock" by using recent panel data from matched Current Population Surveys. We use difference-indifference models to estimate the interaction between having a spouse with employer-based health insurance and potential demand for health care. We find evidence of a larger negative effect of health insurance demand on business creation for those withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(106 citation statements)
references
References 37 publications
5
100
1
Order By: Relevance
“…In addition, Coile and Milligan (2009) show that the death of a spouse and the experience of an acute health condition, like a stroke, are associated with a significant portfolio rebalancing. In line with the notion that a reduced exposure to background risk should make individuals more willing to bear other risks, Fairlie, Gates and Kapur (2011) find that business ownership rates increase from just under age 65 to just over age 65. 5 Card, Dobkin and Maestas (2009) find that Medicare eligibility significantly reduces the death rate of severely ill patients who are admitted to hospitals through the emergency department for non-deferrable conditions.…”
supporting
confidence: 69%
“…In addition, Coile and Milligan (2009) show that the death of a spouse and the experience of an acute health condition, like a stroke, are associated with a significant portfolio rebalancing. In line with the notion that a reduced exposure to background risk should make individuals more willing to bear other risks, Fairlie, Gates and Kapur (2011) find that business ownership rates increase from just under age 65 to just over age 65. 5 Card, Dobkin and Maestas (2009) find that Medicare eligibility significantly reduces the death rate of severely ill patients who are admitted to hospitals through the emergency department for non-deferrable conditions.…”
supporting
confidence: 69%
“…In this section, we take a step back and re-estimate the same hazard rate model, but exclude the HICD and directly include factors that determine the HICD amount instead. This approach is comparable to the extant literature for the USA, which does not calculate a HICD (Holtz-Eakin et al, 1996;Wellington, 2001;Zissimopoulos and Karoly, 2007;Fairlie et al, 2011). Table 5 shows the probit coefficients for the full sample and separately for men and women; average marginal effects of the most interesting variables appear in the rightmost three columns of Table A 3 in Appendix A.…”
Section: The Effect Of Health and The Family Situation On Entry Into supporting
confidence: 56%
“…Some research has suggested broader insurance coverage increases worker mobility and facilitates appropriate risktaking in the labor market (for example, Farooq and Kugler 2016). Providing better coverage options outside the workplace may also facilitate entrepreneurship (Fairlie, Kapur, and Gates 2011;DeCicca 2010); enable workers to invest in additional years of education (Dillender 2014); or give workers additional flexibility in structuring their work lives, such as by retiring when it makes sense for them or reducing their work hours in order to have more time to care for a family member (for example, Heim and Lin 2016).…”
Section: Continued Labor Market Recoverymentioning
confidence: 99%